Tourism Development Strategy in Wewengkon Adat Kesepuhan Citorek as A Tourist Attraction in Lebak Regency - Nur Sahroniah; nurlela Sari; Diah Prihartini; Mulkiah Nurazizah; Sutriyani Adinda Putri; Hikmayatul Muslimah; Aliyah Aliyah; Bryan Alberto; Firdaus Firdaus; Belardo Prasetya Mega Jaya (EQUATOR SINAR AKADEMIA, 2022)
Community service is integrated with the online KKM of Sultan Ageng Tirtayasa University. Which aims to increase the attractiveness of tourists to come to tourism in Wewengkon Adat Kasepuhan Citorek. There are natural attractions, namely Mount Luhur (The Country above the Clouds), Mount Keneng and Strawberry Gardens. The attractiveness of tourists in the tourism sector must of course be improved so that the economy of the surrounding community recovers, therefore a strategy is needed that can attract tourists to come to the tour, many facilities must be added such as photo spots, camping, typical food of Wewengkon Adat Kasepuhan Citorek and also road infrastructure improvement. To introduce tourism in the Kesepuhan Citorek Traditional Wewengkon, we can promote it through existing social media, such as YouTube, Facebook, Instagram, Twitter and others. As well as making a tourist Vlog Video as one of the activities included in the main program in the field of governance carried out by KKM students group 4 Citorek Sabrang Village